Pengaruh Cekaman Kekeringan Terhadap Kandungan Klorofil dan Prolin Daun Kedelai - Rosawanti, Pienyani (Anterior Jurnal, 2016)
The study of physiological responses of soybean to drought stress could be a useful tool to the understanding of the mechanisms of drought resistance. Study was conducted to evaluate the effect of water stress on chlorophyll and prolin accumulation rate. This study was conducted in the Cikabayan greenhouse IPB using ten genotypes of soybean (Ratai, Seulawah, Slamet, Tanggamus, Wilis, GC 22-10, PG 57-1, SC 21-5, SC 39-1, SP 30-4) and PEG (0%, 20%). The result showed that drought stress with PEG simulation significant effect on chlorophyll and proline content.